The Role National Narcotics Agency in Outpatient Rehabilitation in Drug Users Based on The Law Number 17 of 2023 Concering Health - Riend Afrianita; Irsyam Risdawati; Redyanto Sidi (Journal Evidence Of Law, 2026)
This study aims to examine the role of the National Narcotics Agency (BNN) in outpatient rehabilitation programs for drug users based on Law Number 17 of 2023 concerning Health. This law provides a clear legal framework regarding medical and social rehabilitation for drug abusers, including access to outpatient rehabilitation services. This research employs a qualitative approach using in-depth interviews and literature review techniques to explore the role of BNN in implementing rehabilitation programs, the challenges encountered, and the effectiveness of the program in reducing the negative impacts of drug abuse. The results of the study indicate that BNN plays an important role in providing outpatient rehabilitation services aimed at helping drug users regain normal functioning within society. This program involves medical and psychosocial services focused on recovery without requiring inpatient treatment. The implementation of outpatient rehabilitation programs by BNN emphasizes education, assistance, and medical as well as psychological treatment for individuals involved in drug abuse.However, the implementation faces several challenges, including limited rehabilitation facilities, a lack of trained human resources, and persistent social stigma attached to drug users. In addition, although Law Number 17 of 2023 provides a strong legal foundation, challenges remain in terms of inter-agency coordination and the availability of rehabilitation services that are affordable and accessible to the wider community. This study highlights the importance of BNN’s role in improving access to rehabilitation for drug abusers and provides recommendations to strengthen collaboration among the government, non-governmental organizations, and communities in supporting the success of rehabilitation programs. The study concludes that the National Narcotics Agency has a crucial role in outpatient rehabilitation for drug users in accordance with the mandate provided by Law Number 17 of 2023.